2018
DOI: 10.1186/s12974-018-1079-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of glucocorticoid, interleukin-1β, and antioxidants in prenatal stress effects on embryonic microglia

Abstract: Maternal stress during pregnancy is associated with an increased risk of psychopathology in offspring. Resident immune cells of the brain, microglia, may be mediators of prenatal stress and altered neurodevelopment. Here, we demonstrate that neither the exogenous pro-inflammatory cytokine, interleukin-1β (IL-1β), nor the glucocorticoid hormone, corticosterone, recapitulated the full effects of prenatal stress on the morphology of microglial cells in the cortical plate of embryonic mice; IL-1β effects showed gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 33 publications
0
20
2
Order By: Relevance
“…At the molecular level, one can speculate epigenetic programming early in development may render genetic controls different at later points in development, such as shown with maternal grooming on GR methylation [113]. At a cellular level, one might look toward changes in immune cells such as microglia where long-term changes in cell numbers might result from early stimuli [123,124]. Another group of cells to consider are those involved in neurovascular units.…”
Section: Puberty and Pvnmentioning
confidence: 99%
“…At the molecular level, one can speculate epigenetic programming early in development may render genetic controls different at later points in development, such as shown with maternal grooming on GR methylation [113]. At a cellular level, one might look toward changes in immune cells such as microglia where long-term changes in cell numbers might result from early stimuli [123,124]. Another group of cells to consider are those involved in neurovascular units.…”
Section: Puberty and Pvnmentioning
confidence: 99%
“…An increase in circulating pro-inflammatory cytokines is one of the hallmarks of pregnancy complications 55,56 and can be detected in pregnant women experiencing psychological stress 50,57,58 . In animal models, systemic administration of particular cytokines in circulation, such as IL-6 and IL-1β, is sufficient to recapitulate specific offspring neuroimmune abnormalities seen with prenatal stress 59,60 . Interestingly, while psychological stress is thought to induce cytokine production in animal models (and is frequently described in placental and offspring brain tissue, including by our group 25,42 ), few, if any, studies have reported maternal circulating cytokine levels.…”
Section: Discussionmentioning
confidence: 99%
“…Animal modeling of prenatal stress has revealed that maternal inflammatory pathways may be responsible for offspring behavioral abnormalities 59,60,64 , yet potential contribution of disrupted leukocyte populations in maternal circulation or at the maternal-fetal interface have received little attention in this context. Some have demonstrated conflicting results of prenatal social stress on blood monocyte counts in rats 54 and swine 65 , and no change in neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with N-acetyl cysteine (NAC), a glutathione precursor and powerful antioxidant, during the prenatal period as an antioxidant supplement reverses brain redox changes after prenatal stress in adult mice (Bernhardt et al, 2017) and reverses effects of prenatal stress on embryonic microglia (Bittle and Stevens, 2018). However, what remains to be examined is the efficacy of maternal antioxidant treatments during prenatal stress altering the redox balance in the embryonic brain and the behavioral outcomes of adult offspring.…”
Section: Prenatal and Postnatal Antioxidants As Manipulators Of Redoxmentioning
confidence: 99%
“…Because of the importance of this physiology (Bittle and Stevens, 2018), we set out to elucidate maternal factors that underlie the effects of prenatal stress on embryonic microglia in a mouse model. One maternal physiological component of prenatal stress is elevation of plasma corticosterone levels (Gomez-Gonzalez and Escobar, 2010).…”
Section: Maternal Immune Activation (Mia) and Microgliamentioning
confidence: 99%